Pemberdayaan Usaha Anggota Koperasi Kobamie Kendal Melalui Digital Marketing Sebagai Upaya Peningkatan Penjualan - Pitaloka, Lola Kurnia; Feriady, Muhammad (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2023)
The bakery and noodle cooperative is one of the new production cooperatives in Kendal. With his new age, the enthusiasm of the members to develop the cooperative is very high. Unfortunately, they do not have enough knowledge about digitalization, one of which is digital marketing. Marketing is needed by all fields of industry and current.ly marketing is more directed towards digitalization with social media for example. Digital marketing is not as simple as offline marketing which causes difficulties for Kobamie Kendal cooperative members. This service will focus on providing material and training related to digital marketing which includes practice in operating algorithms to get the right target market for the business development of Kobamie Kendal cooperative members. The service method usesd is a discussion session and workshop with in-depth evaluation and observation that will be carried out after the workshop is over. The service team directs social media for Kobamie cooperative members and creates websites. Provision of practical material focusing on social media specialists with social media algorithms. The website was created to contain the production of cooperative members so that it will become e-commerce for Kobamie Kendal cooperative members.